Estimation of Critical Components of Internet Infrastructure - Kajackas, A.; Rainys, R. (Elektronika ir Elektrotechnika, 2011)
The article analyses the connectivity of Internet - one of the fundamental network characteristics - on the basis of network topology analysis. The metrics compiled allows identifying the critical elements of Internet network infrastructure: critical and ɳ-critical nodes and critical as well as critical and k-critical links. The model of monitoring the critical network elements was created, and the algorithm of realizing was described. Ill. 1, bibl. 11, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.282